Regulation of cellular gene expression by nanomaterials - Sang Hun Chun; Ji Soo Yuk; Soong Ho Um (Nano Convergence, 2018)
Abstract Within a cell there are several mechanisms to regulate gene expression during cellular metabolism, growth, and differentiation. If these do not work properly, the cells will die or develop abnormally and, in some cases, even develop into tumors. Thus, a variety of exogenous and endogenous approaches have been developed that act on essential stages of transcription and translation by affecting the regulation of gene expression in an intended manner. To date, some anticancer strategies have focused on targeting abnormally overexpressed genes termed oncogenes, which have lost the ability to tune gene expression. With the rapid advent of nanotechnology, a few synthetic nanomaterials are being used as gene regulation systems. In many cases, these materials have been employed as nanocarriers to deliver key molecules such as silencing RNAs or antisense oligonucleotides into target cells, but some nanomaterials may be able to effectively modulate gene expression due to their characteristic properties, which include tunable physicochemical properties due to their malleable size and shape. This technology has improved the performance of existing approaches for regulating gene expression and led to the development of new types of advanced regulatory systems. In this short review, we will present some nanomaterials currently used in novel gene regulation systems, focusing on their basic features and practical applications. Based on these findings, it is further envisioned that next-generation gene expression regulation systems involving such nanomaterials will be developed.